2014
DOI: 10.3732/apps.1300085
|View full text |Cite
|
Sign up to set email alerts
|

A target enrichment method for gathering phylogenetic information from hundreds of loci: An example from the Compositae

Abstract: • Premise of the study: The Compositae (Asteraceae) are a large and diverse family of plants, and the most comprehensive phylogeny to date is a meta-tree based on 10 chloroplast loci that has several major unresolved nodes. We describe the development of an approach that enables the rapid sequencing of large numbers of orthologous nuclear loci to facilitate efficient phylogenomic analyses.• Methods and Results: We designed a set of sequence capture probes that target conserved orthologous sequences in the Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
254
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(261 citation statements)
references
References 25 publications
6
254
0
1
Order By: Relevance
“…A phylogenomic approach targeting thousands of independently evolved nuclear loci may be the only way to assess the current taxonomy of this group, and dissect the roles of hybridization and introgression in the origin and rapid diversification of this insular lineage. Phylogenomic methods based on markers identified from, e.g., restriction site associated DNA sequencing (RADseq) (Cruaud et al, 2014;Eaton and Ree, 2013;Smith et al, 2014), targeted enrichment of ultraconserved elements (UCEs) or conserved ortholog sequences (COS) (Mandel et al, 2014;Smith et al, 2014), and RNA-Seq (Wen et al, 2013;Wickett et al, 2014) could be suitable methods to resolve Hawaiian mint relationships. However, these approaches are also associated with challenges, including accurately inferring orthology in high polyploid plants, slow mutation rates in exonic regions, which may be too low to resolve recent radiations (Giarla and Esselstyn, 2015), and the need to obtaining high quality RNA and DNA.…”
Section: Resultsmentioning
confidence: 99%
“…A phylogenomic approach targeting thousands of independently evolved nuclear loci may be the only way to assess the current taxonomy of this group, and dissect the roles of hybridization and introgression in the origin and rapid diversification of this insular lineage. Phylogenomic methods based on markers identified from, e.g., restriction site associated DNA sequencing (RADseq) (Cruaud et al, 2014;Eaton and Ree, 2013;Smith et al, 2014), targeted enrichment of ultraconserved elements (UCEs) or conserved ortholog sequences (COS) (Mandel et al, 2014;Smith et al, 2014), and RNA-Seq (Wen et al, 2013;Wickett et al, 2014) could be suitable methods to resolve Hawaiian mint relationships. However, these approaches are also associated with challenges, including accurately inferring orthology in high polyploid plants, slow mutation rates in exonic regions, which may be too low to resolve recent radiations (Giarla and Esselstyn, 2015), and the need to obtaining high quality RNA and DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence capture was performed using a custom probe set, MyBaits designed by MYcroarray (Ann Arbor, Michigan, USA) and described in Mandel et al (2014). DNA libraries were checked for quality using 2100 Bioanalyzer (Agilent, Santa Clara, California, USA), quantified using a Qubit 2.0 Fluorometer (Life Technologies, Grand Island, New York, USA), pooled, and sequenced on either two lanes of an Illumina HiSeq 2000 sequencer (2 Â 100 bp read length) or one run of the Illumina MiSeq sequencer (2 Â 250 bp read length).…”
Section: Taxon Samplingmentioning
confidence: 99%
“…All of these studies are hampered by the unresolved areas of the base tree. Mandel et al (2014) previously demonstrated the utility of sequence capture and NGS for resolving relationships within the family. Here we expand upon that previous work by considering multi-copy genes in our data set using a clustering approach, during orthology detection prior to gene-tree phylogenetic analysis.…”
mentioning
confidence: 99%
See 2 more Smart Citations